The Effect of Omnichannel Customer Experience on Purchase Decision: The Mediating Role of Perceived Value - Sjukun Sjukun; Wily Julitawaty; Widalicin Januarty; Fitria Halim; Yusuf Taufik (CV. Ulil Albab Corp, 2026)
The expansion of omnichannel retail practices has significantly changed the way consumers interact with brands and determine their purchasing choices. This study aims to analyze the effect of integrated cross-channel experiences on consumer buying decisions by considering perceived value as a mediating variable. The research adopts a quantitative explanatory approach using a survey method. Data were obtained from consumers who had prior experience shopping through both digital and physical retail channels. Participants were selected through purposive sampling, resulting in a sample of around 100 respondents. The collected data were examined using regression analysis and mediation analysis with the PROCESS Macro technique. The results indicate that integrated shopping experiences across multiple channels positively and significantly influence consumer buying decisions. In addition, cross-channel experience also exerts a significant effect on consumers’ perceived value, which subsequently encourages stronger purchasing decisions. The mediation analysis confirms that perceived value partially explains the relationship between integrated shopping experiences and buying decisions. These findings imply that consumers are more likely to develop stronger purchase confidence when retailers provide smooth, coordinated, and convenient experiences across various channels. From a theoretical perspective, this study enriches marketing research by combining experiential and value-oriented approaches to explain consumer behavior in integrated retail environments. Practically, the findings offer useful insights for companies seeking to strengthen channel coordination, maintain information consistency, and improve transaction efficiency in order to maximize customer experience quality within omnichannel retail systems.